A China in Transition: The Rhetoric and Substance of Chinese Foreign Policy under Xi Jinping. Issue 2 (4th May 2017) - Poh, Angela; Li, Mingjiang
ABSTRACT: Has China under Xi Jinping bid an official farewell to Deng Xiaoping's "lying low" international strategy (taoguang yanghui) in pursuit of a more ambitious foreign policy agenda? In this article, we contend that Xi's foreign policy is indeed beginning to show signs of departure from that of his predecessors. Beijing has displayed intentions to gradually create new rules in international politics and reform major international institutions to better suit Chinese interests. However, Chinese foreign policy in the first term of Xi's administration has remained in a transitory phase. Continued domestic preoccupations, China's lack of experience in undertaking more international responsibilities, as well as conflicting economic and security imperatives in China's neighborhood have constrained the Chinese leadership's ability to completely abandon its "lying low" international strategy.